Assessment of E-Commerce in Nigeria in the Light of Māliki Jurisprudence - Musa-Jeje Ibrahim Aladire (Universitas Darussalam Gontor, 2024)
Prior to the introduction of paper money and modern banking, bartering in the context of directly trading goods and services was used. This barter system was incredibly effective, which may explain why it was used for centuries without obvious need to be replaced. However, as more advanced mode of production and rapidly expanding markets have emerged, it becomes increasingly ineffective. As a result, alternative means of exchange were invented, resulting in the development of paper money issued by the government and banks, making financial transactions more transparent and controlled. Central banks started printing paper in different denominations. Today, the vast majority of national currencies are non-convertible fiat. With the advent of knowledge and communication technologies in the twenty first century, many countries shifted to the online business activities. The method employed in this paper historical and analytical. Historically, the paper tends to unravel the historical event that are pertinent to the topic while analytical methods is meant to analyze the finds from the historical events, it ends with conclusion and recommendation’s. The researcher relies on journals, textbooks, magazines, internet materials.